Efektifitas Strategi Pembelajaran PAI Berbasis Islam Moderat dalam Mencegah Bullying di Lembaga Pendidikan - Solichah, Siti Maratus; Shohib, Muhammad (Lembaga Yasin AlSys, 2025)
The phenomenon of bullying in educational settings, particularly at the junior high school level, presents a significant issue that adversely affects students' social and psychological development. One strategic approach to addressing this problem is through the integration of moderate Islamic values into Islamic Religious Education (PAI) learning strategies. This study aims to analyze the effectiveness of PAI learning strategies based on moderate Islam in preventing bullying in schools. The research employs a qualitative approach with a case study method, focusing on the teaching practices of Islamic Education teachers at UPT SMP Negeri 3 Gresik. Data were collected through observation, in-depth interviews, and documentation, with the primary informants being PAI teachers and eighth-grade students. The results indicate that problem-based learning strategies, integrated with moderate Islamic values (such as tawassuth, tasamuh, i’tidal, and syura), significantly enhance tolerance, reduce aggressive behavior, and foster a more inclusive and harmonious learning environment. The study concludes that PAI learning that internalizes the values of religious moderation plays a crucial role in preventing bullying in schools. The implications of these findings underscore the importance of strengthening school culture programs and the active role of PAI teachers as agents of change in promoting a friendly and humane educational environment.